2018
DOI: 10.1515/bjreecm-2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Empirical Studies on FDI Determinants

Abstract: Unlike the other forms of investment strategies, foreign direct investment (FDI) involves the long-term commitment in the host country. FDI determinants are complex and multi-dimensional phenomena that result from both macro-economic and firm strategy considerations. The main objective of the present research is to review the empirical studies on FDI determinants in order to find out what motives international corporations are pursuing since the FDI policies and nation-specific business environment are directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
0
8
0
2
Order By: Relevance
“…There is a well-established academic literature that points to a large number of factors that determine FDI inflows especially into emerging and developing economies (See Blonigen, 2005 for a comprehensive review of this literature). Studies such as Sahoo (2012) and Sahiti et al (2018) have identified market size, labour cost, trade openness, infrastructure, economic reforms and labour quality as determining factors for FDI inflows. One of the many determinants on FDI relates to the movement of exchange rates both in terms of level and volatility.…”
Section: Figure 1 Fdi Inflows To India (Us$ Billion) and As A Percenmentioning
confidence: 99%
“…There is a well-established academic literature that points to a large number of factors that determine FDI inflows especially into emerging and developing economies (See Blonigen, 2005 for a comprehensive review of this literature). Studies such as Sahoo (2012) and Sahiti et al (2018) have identified market size, labour cost, trade openness, infrastructure, economic reforms and labour quality as determining factors for FDI inflows. One of the many determinants on FDI relates to the movement of exchange rates both in terms of level and volatility.…”
Section: Figure 1 Fdi Inflows To India (Us$ Billion) and As A Percenmentioning
confidence: 99%
“…A liberdade de decisão viabiliza o envolvimento dos jogadores com a partida e, consequentemente, a ascensão de experiências emocionais a partir da interação entre os participantes e o cenário do jogo (Stieler-Hunt et al, 2014). A autonomia garantida ao jogadores durante a partida também possibilita ressignificar experiências externas (Brougère, 2002), bem como valorizar a singularidade de cada participante, tornando as partidas inéditas (Zeng & Shang, 2018).…”
Section: Discussionunclassified
“…Esta aproximação motiva o compartilhamento de experiências similares, de forma a promover a ressignificação e a transformação das vivências. O fato de os jogos retratarem situações cotidianas favorece o vínculo e a imersão dos participantes, criando um espaço propício para a transferência e a utilização do conhecimento (Zeng & Shang, 2018) produzido previamente ou gerado na partida.…”
Section: Discussionunclassified
“…In one way or another, a vast majority of countries aiming for accelerated growth of their economies have been dependent on foreign capital investment regardless of the market size or its development (Sahiti et al, 2017), and it is almost unimaginable that such a thing would be accomplished nowadays without addressing this form of investment. Host countries adopt friendly FDI policies and provide different incentives to meet investors' expectations (Sahiti et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%